The development of a Self-Rated ICF-based questionnaire (HEAR-COMMAND Tool) to evaluate Hearing, Communication, and Conversation disability: Multinational experts’ and patients’ perspectives - Afghah, Tahereh; Alfakir, Razan; Meis, Markus; van Leeuwen, Lisette; Kramer, Sophia E.; Hammady, Mahmoud; Youssif, Mostafa; Wagener, Kirsten C. (Frontiers in Rehabilitation Sciences, 2022)
Objective: An instrument that facilitates the advancement of hearing healthcare delivery from a biomedical model to a biopsychosocial one that underpins the International Classification of Functioning, Disability, and Health framework (ICF) brief and comprehensive Core Sets for Hearing Loss (CSHL) is currently unavailable. The objective is to describe the process of developing and validating a new questionnaire named the HEAR-COMMAND Tool created by transferring the ICF CSHL into a theory-supported, practically manageable concept. Design: A team from Germany, the USA, the Netherlands, and Egypt collaborated on development. The following ICF domains were considered; “Body Functions” (BF), “Activities and Participation” (AP), and “Environmental Factors” (EF). The development yielded English, German, and Arabic versions. A pilot validation study with a total of 109 respondents across three countries, Germany, Egypt, and the USA was conducted to revise the item terminology according to the feedback provided by the respondents. Results: The questionnaire included a total of 120 items. Ninety items were designed to collect information on the functioning and 30 items inquiring about demographic information, hearing status, and Personal Factors. Except for the “Body Structures” (BS) domain, all the categories of the brief ICF CSHL were covered (a total of 85% of the categories). Moreover, the items covered 44% of the comprehensive ICF CSHL categories including 73% of BF, 55% of AP, and 27% of EF domains. Overall, the terminology of 24 ICF-based items was revised based on the qualitative analysis of the respondents’ feedback to further clarify the items that were found to be unclear or misleading. The tool highlighted the broad connection of HL with bodily health and contextual factors. Conclusions: The HEAR-COMMAND Tool was developed based on the ICF CSHL and from multinational experts’ and patients’ perspectives with the aim to improve the execution of audiological services, treatment, and rehabilitation for adult patients with HL. Additional validation of the tool is ongoing. The next step would be to pair the tool with BS categories since it was excluded from the tool and determine its effectiveness in guiding hearing health care practitioners to holistically classify categories influencing hearing, communication, and conversation disability.